Effects of flexible ureteroscopy on kidney: A prospective clinical trial - Ertaş, Kasım (Turk J Urol, 2020)
OBJECTIVE: To investigate the effects of flexible ureteroscopy (F-URS) on the operated side of a kidney by assessing the renal damage markers, urine neutrophil gelatinase-related lipocalin (NGAL) and serum cystatin-C (Cys-C), and overall kidney function with the measurements of standard serum creatinine and urine albumin and protein levels. MATERIAL AND METHODS: A total of 30 patients who underwent F-URS for treatment of upper urinary stone disease were prospectively evaluated. Preoperative serum urea, creatinine, and Cys-C levels were noted. Levels of urine albumin, protein, creatinine, and NGAL in spot urine samples from the operated side of a kidney obtained through the access sheath preoperatively and through the ureteral catheter 1 and 24 hours postoperatively were also measured. Preoperative and postoperative parameter levels were statistically compared. RESULTS: The patients’ mean age was 46.6±15.9 years. The mean operative and fluoroscopy times were 90.67±32.5 and 3.15±1.43 minutes, respectively. The urine creatinine, albumin, protein, albumin/creatinine, and protein/creatinine levels were similar in preoperative and postoperative periods. Postoperative serum urea, creatinine, and Cys-C levels and urine NGAL and NGAL/creatinine levels were not also found with remarkable changes from the baseline levels. CONCLUSION: F-URS is a safe therapeutic intervention in the treatment of urolithiasis, especially regarding renal damage, and functional outcomes.